THE EFFECTIVENESS OF HYPNOTHERAPY TO REDUCE ANXIETY IN PRE-CAESAREAN SECTION WOMEN - Mubarokah, Rizka Innayatun; Prasetya, Hanung; Respati, Supriyadi Hari (Journal of Maternal and Child Health, 2020)
Background: Anxiety felt by women before delivery with cesarean section can cause psychological problem, increase pain in surgery, increase analgesic needs, and prolong hospital treatment. Hypnotherapy has minimal side effects and is easy to do in reducing anxiety. The purpose of this study was to analyze the effect of hypnotherapy in reducing anxiety in women with pre-cesarean section.Subjects and Method: This was a randomized controlled trial study conducted at in Karanganyar Hospital, and PKU Muhammadiyah Hospital, Karanganyar, Central Java, from July to August 2019. A sample of 60 women was selected for this study by purposive sampling. 30 subjects of the treatment group received hypnotherapy intervention and 30 subjects of the control group received standard care. The dependent variable was anxiety. The independent variable was hypnotherapy. Anxiety was tested by the Hamilton Rating Scale for Anxiety questionnaire. Hypnotherapy was done using hypnosis recording/audio. The data were analyzed by independent t test.Results: Mean of anxiety after hypnotherapy (mean = 14.17; SD = 4.36) was lower than control group (mean = 19.93; SD = 6.02), effect size = -1.09, and is statistically significant (p <0.001).Conclusion: Hypnotherapy is effective in reducing anxiety in women before cesarean section.Keywords: anxiety, hypnotherapy, cesarean sectionCorrespondence: Rizka Innayatun Mubarokah. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: rizka.inn@gmail.com. Mobile: 082240337404Journal of Maternal and Child Health (2020), 5(1): 12-18https://doi.org/10.26911/thejmch.2020.05.01.02